A history of the sub-order Cystonectae (Hydrozoa: Siphonophorae) - Pugh, P. R. (Zootaxa, 2019)
The siphonophore sub-order Cystonectae presently comprises just five species in three genera and two families, and includes Physalia physalis, the Portuguese Man O’War. Despite the smallness of the group its history has been very chequered, particularly for P. physalis, which has been described under more than fifty different names. Haeckel (1888) was one of the worst offenders regarding the description of questionable species, but even Totton (1965) was uncertain as to the validity of some previously described cystonect species. Herein, an attempt has been made to review the history of the sub-order Cystonectae and to clarify its taxonomy. A list of synonyms for each recognised cystonect species is given in an appendix.